Applications of Fourier Series and Fourier Transformation - Shah, Yogendra Prasad (Cognition, 2019)
This paper investigates into the application of fourier transformation and series, which converts time domain signal to frequency domain signals, at which signals can be analyzed. Unlike Laplace transform, Fourier Transforms does not have full S plane, it just have the frequency j2πf plane. Fourier Transforms helps to analyze spectrum of the signals, helps in find the response of the LTI systems. (Continuous Time Fourier Transforms is for Analog signals and Discrete time Fourier Transforms is for discrete signals). Discrete Fourier Transforms are helpful in Digital signal processing for making convolution and many other signal manipulations. Overall, the paper will conclude the impact of Fourier Transforms in life.